(untitled) (Italiano LinguaDue, 2018)
Il tipo di testo “voce lessicografica digitale”, molto strutturato, dovrebbe esser studiato fra i tipi di testo. Servirebbe a controbilanciare una diffusa credenza secondo cui la consultazione dei dizionari digitali online è talmente facile da non richiedere una specifica propedeutica. In questo contributo tratteremo dell’allenamento a usare dizionari interrogabili per intero con modalità tutto testo ed eventuale ricerca avanzata. In particolare si commenteranno gli esercizi pensati per allenare a ricerche in dizionari dell’Ottocento come il Tommaseo-Bellini o la quarta e quinta edizione del Vocabolario dell’Accademia della Crusca, anche partendo da brani letterari. Non sempre è indispensabile ricorrere alla consultazione di un dizionario per svolgere questi esercizi, ma pensiamo che le esercitazioni nel loro insieme siano un esempio di come fare (storia della) lingua italiana facendo letteratura italiana e imparando a fare ricerche in basi di dati in rete, quali i dizionari digitali di fatto sono. The history of Italian language through lexicons of the xix century in the network As a type of text the “digital dictionary entry” is very complex and should be studied as a text type. It should be explained in classes dealing with text types in order to counterbalance the widespread belief that looking up material in digital dictionaries is easy and therefore there is no need for explanation or specific training. In this paper we present and discuss training exercises to exploit pieces of information contained in Eighteenth and Nineteenth centuries dictionaries freely accesible on-line such as Tommaseo-Bellini, fourth and fifth editions of Vocabolario degli Accademici della Crusca. We will show exercises designed to start from literary passages. It is not always necessary to use dictionaries in order to carry out proposed tasks, but we believe that such tasks help to explain to users the history of Italian language through Italian literature and that they are all the more useful since the users must conduct searches on those online databases, which is what digital dictionaries are.